Investasi Bijak: Bagaimana Pengetahuan Keuangan dan Literasi Keuangan Mempengaruhi Keputusan Investasi Guru Di Kota Palangka Raya Dengan Minat Investasi Sebagai Mediasi - Solikah Nurwati; Ani Mahrita; Noorjaya Nahan; Achmad Syamsudin; Peridawaty Peridawaty (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The development of financial technology and increasing public access to investment instruments, encourage the participation of various professional groups to invest in the capital market. Teachers who are classified as employees and professionals have a lower level of financial literacy compared to other professions, so the population of this study is active ASN status teachers at SMAN Palangka Raya City = 538 people, with a random sample obtained 100 teachers. Analysis with Smart PLS version 4.0. Using four latent variables; two endogenous variables (investment knowledge and financial literacy); one moderating variable (investment interest) and one exogenous variable (investment decision). The four variables were analyzed for their direct and indirect influence between endogenous, moderating, and exogenous variables. The output results of R²: 1) investment interest = 0.182 (weak), 2). Investment decision = 0.218 (weak) and the results of the study show: (1) investment interest is influenced by investment knowledge variables and financial literacy with a positive relationship; 2) financial literacy is able to influence teacher investment decisions with a unidirectional relationship, but investment knowledge and investment interest cannot influence investment decisions; 3) investment interest is not able to act as a link between investment knowledge and financial literacy towards investment decisions of SMAN teachers in Palangka Raya City in the capital market.